FENOMENA PREMANISME DI INSTAGRAM - Iin Soraya (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2019)
The appearance of @lambe_turah pampers Indonesian people who want to know about the news of their idol artists. From the news delivered in the @lambe_turah account, a lot of it pops up in the comments feature of fans of the artist (loper) and those who don't like the artist (haters). The nitizen comments on the @lambe_turah account lead to negative sentiments, not infrequently using harsh words, provocations, even to the point of using the word sarcasm to thuggery in his comments. This study uses the constructivism paradigm. The nature of this research is descriptive, with a qualitative research approach. Research methods use phenomenology. The theories used in this study are phenomenology theory, constructivism theory and symbolic interaction theory. The results of this study are that there is thuggery in the use of captions which can controversially provoke nitizen comments. The negative comments from the frontiers that lead to the emergence of pramanism on Instagram with the use of harsh and frontal language words resulted in the emergence of thuggery on Instagram. Social media thuggery is displayed in a verbal form, namely the word contained. Social media thuggery happens not because it is intentional, like bullying and ridiculing each other on social media, when there is an argument on social media in the form of discussion or status war in comments, even though there is no physical violence but the social media war can be legal, if one party feels disadvantaged. keywords: Phenomenon, Instagram, Thuggery, Lambe Turah